Insulin sensitizing potential of fractions isolated from X. molluccensis and X. granatum - Renuka Munshi,; Samidha Joshi,; T Narendra,; SPS Bhandari, (International Journal of Phytomedicine, 2015)
The present study was designed to elucidate the anti-hyperglycemic action of two fractions isolated from marine plants i.e., CDR267F018 from X. molluccensis and CDR134F194 from X. granatum in insulin resistant conditions using in vitro and in vivo models. The glucose uptake was studied using in vitro model of 3T3 L1 adipocyte and L-6 skeletal muscle cell line. The effect of fractions was also studied in dexamthazaone induced insulin resistant conditions in 3T3L1 adipocyte model. The in vivo model of insulin resistance was developed using a high fructose diet. Parameters assessed were weight, fasting blood glucose, insulin, cholesterol, triglycerides and liver glycogen content. Pioglitazone was used as a positive control. CDR267F018 and CDR134F194 demonstrated stimulation of glucose uptake in L-6 skeletal muscle cells in a dose dependent manner. Both the fractions per se significantly stimulated the basal 2-deoxyglucose uptake in 3T3L1 model. A stimulation of 2-deoxyglucose uptake was also observed in insulin resistant cells. The effect shown by these drugs was comparable to Pioglitazone, a known insulin sensitizer. Administration of the fractions CDR267F018 and CDR134F194 demonstrated a dose dependent decrease in sugar and insulin levels with maximum effect at the highest dose tested. These fractions also decreased the total cholesterol levels although an increase in triglycerides levels was observed at the higher doses. The maximum decrease in triglycerides was seen with lower dose. CDR267F018 and CDR134F194 have a potential role in ameliorating insulin resistant conditions as seen in the 3T3L1 adipocyte, skeletal muscle and fructose fed model.